2021
DOI: 10.1007/s10895-021-02783-4
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Analysis of Parathyroid and Thyroid Tissues by Ground-State diffuse Reflectance and Laser Induced Luminescence: a Preliminary Report

Abstract: Intraoperative discrimination of thyroid and parathyroid tissues is fundamental in thyroid surgery. Recent uorescence studies have shown stronger NIR emission in parathyroid tissue than in thyroid tissue, presenting a potential avenue for the development of a tool for surgical assistance. However, the uorophore responsible for this emission has not yet been identi ed. In this work, spectroscopic analysis was performed to ascertain the origin of the emission peaks in parathyroid tissue. Ground-state diffuse re … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…Based on these studies, we conclude that NIRAF has a satisfactory parathyroid identification rate, which makes it a reliable auxiliary equipment ( 110 ). In thyroid surgery, NIRAF is also significantly effective in reducing transient hypocalcemia after surgery.…”
Section: Near-infrared Autofluorescence As the Novel Adjunct In Surgerymentioning
confidence: 74%
“…Based on these studies, we conclude that NIRAF has a satisfactory parathyroid identification rate, which makes it a reliable auxiliary equipment ( 110 ). In thyroid surgery, NIRAF is also significantly effective in reducing transient hypocalcemia after surgery.…”
Section: Near-infrared Autofluorescence As the Novel Adjunct In Surgerymentioning
confidence: 74%
“…This autofluorescence allowed for the pre-localization of the PTGs during thyroidectomy. More recently, Serra et al (10), using fluorescence spectrometry and excitation at 650 nm, confirmed that the PTGs emitted autofluorescence at least at 700 nm and that maximum autofluorescence was observed close to 711 nm. In order to avoid using two excitation wavelengths, we examined a single excitation that rebalanced the measured signal levels between ICG and PTG autofluorescence.…”
Section: Discussionmentioning
confidence: 89%
“…Next, a comparison of the emission spectra of PTG autofluorescence for excitation at 650 nm, as provided by Serra (10), with that of ICG (Figure 1) showed that their peak maxima were well separated. We assumed that the autofluorescence spectra for wavelengths longer than 700 nm were similar, with excitation wavelengths of 650 and 685 nm.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…Благодаря недавним исследованиям, связанным с применением индоцианина зеленого (ICG), было установлено, что перфузия ОЩЖ выше чем у ЩЖ [22]. Также существенным является тот факт, что по данным ультразвукового исследования в режиме доплеровского картирования было установлено наличие более интенсивного кровотока в ОЩЖ, чем в лимфатических узлах [23]. В силу того, что кровоснабжение ОЩЖ интенсивнее, чем у окружающих тканей, можно сделать вывод о более высокой температуре данной структуры и, как следствие, о возможности визуализации методом термографии.…”
Section: фундаментальные основы методов флуоресцентной диагностикиunclassified